2022
DOI: 10.1017/s0714980822000198
|View full text |Cite
|
Sign up to set email alerts
|

Passive Remote Monitoring and Aging in Place: A Scoping Review

Abstract: Passive remote monitoring is a relatively new technology that may support older adults to age in place. However, current knowledge about the effectiveness of this technology in extending older adults’ independence is lacking. Therefore, we conducted a scoping review of studies examining passive remote monitoring to systematically synthesize evidence about the technology’s effectiveness as an intervention. Our initial search of Embase, CINAHL, PubMed, and Scopus databases identified 486 unique articles. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The third strategy (n=30 reviews) is to refer to technologies in terms of their intended purpose in caring services or practices that they are part of. Such terms include “teleopthamology” [ 85 ], “monitoring technologies” [ 86 , 87 ], “telerehabilitation” [ 88 - 93 ], “technology for home health care” [ 94 , 95 ], or “technology for pain management” [ 96 ]. Most reviews that relied on this strategy were concerned with telerehabilitation (n=7) or technology for health information (n=6).…”
Section: Resultsmentioning
confidence: 99%
“…The third strategy (n=30 reviews) is to refer to technologies in terms of their intended purpose in caring services or practices that they are part of. Such terms include “teleopthamology” [ 85 ], “monitoring technologies” [ 86 , 87 ], “telerehabilitation” [ 88 - 93 ], “technology for home health care” [ 94 , 95 ], or “technology for pain management” [ 96 ]. Most reviews that relied on this strategy were concerned with telerehabilitation (n=7) or technology for health information (n=6).…”
Section: Resultsmentioning
confidence: 99%
“…Immature technologies will amplify the limitations of remote monitoring, such as asymmetric information between the real world and the digital world, and incorrect information exchange between customers and enterprises (Watson et al, 2020). The manufacturer also does not have a good enough way to show customers the benefits that this technology will bring to customers (Read et al, 2022). Meanwhile, RMT also enables manufacturers to monitor customers indirectly.…”
Section: Research On the Application Of Rmt In Enterprisesmentioning
confidence: 99%
“…...I see often-times a lot of clients need to go to special care homes or nursing homes that do have 24 Clients also reported increased accessibility to emergency services when required and increased peace of mind and sense of security. For example, one of the clients shared their experience using the system to access emergency services when they fell:…”
Section: Impact Of Carelink Advantage On Client Health Outcomesmentioning
confidence: 99%
“…To date, limited research has examined the impact of in-home remote monitoring systems on older adults' ability to live at home longer. A recent scoping review [24] identified only 14 studies published before February 2019 that examined outcomes related to having this type of technology in the homes of community-dwelling older adults. Although a wide range of outcomes was assessed in these studies, none of them tested the impact of passive remote monitoring on the length of time older adults were able to live at home or time until institutionalization was required.…”
Section: Staying Home Longermentioning
confidence: 99%